Using spectacle lenses with embedded rings of high-spherical microlenses Stellest® for the myopia control in children: two-year results - O. V. Proskurina; E. P. Tarutta; N. A. Tarasova; S. V. Milash; S. G. Harutyunyan; G. A. Markosyan (Российский офтальмологический журнал, 2024)
Purpose: to evaluate the effect of wearing glasses with Stellest® lenses on the spherical equivalent of refraction (SER) dynamics, the yearly progression gradient (YPG) and the axial length (AL) of the eye in children with progressive myopia 12, 18 and 24 months after the start of use. Material and methods. The main and the control groups of the study included children aged 8 to 13 years with low to moderate myopia at the beginning of observation. Stellest® glasses (the main group) were prescribed to 35 children with myopia 3.15 ± 0.19 D, while single vision (SV) glasses (the control group) were prescribed to 32 children with myopia 2.68 ± 0.18 D. The dynamics of the SER, YPG, and AL of the eye were assessed. Results. In the main (Stellest®) group, after 24 months of observation, SER increased by ave. 0.20 ± 0.06 D. YPG was shown to decrease in 93.5 % of cases by ave. 0.81 ± 0.05 D. The AL increased by an average of 0.15 ± 0.03 mm. In the control group, after 24 months of observation, the SER averaged 0.95 ± 0.08 D. YPG showed a decrease of ave. 0.38 ± 0.05 D in 61.1 % of cases. The AL of the eye increased by an average of 0.48 ± 0.04 mm. Conclusion. Stellest® glasses, if worn constantly, effectively slow myopia progression and axial elongation as compared with SV glasses. By the end of the follow-up period, in the Stelest® group, SER showed an increase by 79 % less than in the control group of SV glasses, and the AL showed increase in the length of the eye which was 69 % less than in the control group. Over the 24 months’ wearing of Stellest® glasses, YPG turned out to be 4.8 times lower than in the control group.